Dissemination of blaNDM–1 Gene Among Several Klebsiella pneumoniae Sequence Types in Mexico Associated With Horizontal Transfer Mediated by IncF-Like Plasmids - Toledano-Tableros, José Eduardo; Gayosso-Vázquez, Catalina; Jarillo-Quijada, Ma Dolores; Fernández-Vázquez, José Luis; Morfin-Otero, Rayo; Rodríguez-Noriega, Eduardo; Giono-Cerezo, Silvia; Gutkind, Gabriel; Di Conza, José; Santos-Preciado, José Ignacio; Alcántar-Curiel, María Dolores (Frontiers in Microbiology, 2021)
Nosocomial infections caused by multidrug-resistant (MDR) Klebsiella pneumoniae are a major health problem worldwide. The aim of this study were to describe NDM-1-producing K. pneumoniae strains causing bacteremia in a tertiary referral hospital in Mexico. MDR K. pneumoniae isolates were screened by polymerase chain reaction (PCR) for the presence of resistance genes. In resistant isolates, plasmids were identified and conjugation assays were performed. Clonal diversity and the sequence types were determined by pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST). A total of 80 K. pneumoniae isolates were collected from patients with bacteremia over a one-year period. These isolates showed a level of resistance of 56% (47/80) to aztreonam, 56-60% (45-48 / 80) to cephalosporins, 53% (36/80) to colistin and 13% (10/80) to carbapenems. The carbapenem resistant isolates were blaNDM-1 carriers and negative for blaKPC, blaNDM, blaIMP, blaVIM and blaOXA-48-like carbapenemases genes. Conjugative plasmids IncFIIA and IncF group with sizes of 82-195 kbp were carriers of blaNDM-1, blaCTX-M-15, blaTEM-1, aac(6’)-Ib and/or aac(3’)-IIa. Clonal variability and nine different multilocus sequence types were detected (ST661, ST683, ST1395, ST2706, ST252, ST1198, ST690, ST1535 and ST3368) for the first time in the isolates carrying blaNDM-1 in Mexico. This study demonstrates that blaNDM-1 has remained within this hospital in recent years and suggests that it is currently the most prevalent carbapenemase among K. pneumoniae MDR strains causing bacteraemia in Mexico. The horizontal transfer of blaNDM-1 gene through IncF-like plasmids among different clones demonstrates the dissemination pathway of antimicrobial resistance and underscore the need for strong and urgent joint measures to control the spread of NDM-1 carbapenemase in the hospital.